1996
DOI: 10.1128/mcb.16.7.3317
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins That Interact with Exon Sequences, Splice Sites, and the Branchpoint Sequence during Each Stage of Spliceosome Assembly

Abstract: We have carried out a systematic analysis of the proteins that interact with specific intron and exon sequences during each stage of mammalian spliceosome assembly. This was achieved by site-specifically labeling individual nucleotides within the 5 and 3 splice sites, the branchpoint sequence (BPS), or the exons with 32 P and identifying UV-cross-linked proteins in the E, A, B, or C spliceosomal complex. Significantly, two members of the SR family of splicing factors, which are known to promote E-complex assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
97
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 42 publications
10
97
1
Order By: Relevance
“…Identification of the p25 cross-link as SRp20 is consistent with a previous report from the Reed laboratory (Chiara et al 1996) that SRp20 (and SRp30) could be cross-linked in the E/CC complex at positions −31 and −26 relative to the 5Ј splice site of AdML pre-mRNA. We similarly reported that SRp20 cross-links to position −2 of PIP pre-mRNA independent of splicing (Le Hir et al 2000a).…”
Section: Enhanced 5ј Exon Association Of Ref/aly and Srp20 Upon Exon supporting
confidence: 78%
See 1 more Smart Citation
“…Identification of the p25 cross-link as SRp20 is consistent with a previous report from the Reed laboratory (Chiara et al 1996) that SRp20 (and SRp30) could be cross-linked in the E/CC complex at positions −31 and −26 relative to the 5Ј splice site of AdML pre-mRNA. We similarly reported that SRp20 cross-links to position −2 of PIP pre-mRNA independent of splicing (Le Hir et al 2000a).…”
Section: Enhanced 5ј Exon Association Of Ref/aly and Srp20 Upon Exon supporting
confidence: 78%
“…The p220 that cross-linked to benzophenone at position −7 is most likely hPrp8p, as we and others have previously demonstrated that hPrp8p cross-links strongly near the end of the 5Ј exon and at the 5Ј splice site (Chiara et al 1996 and references therein; Reyes et al 1999;Le Hir et al 2000a). Likewise, the p170 that cross-linked only after exon ligation may well be SRm160-using a different antiserum from that used here (see Materials and Methods), we have previously shown that SRm160 can become cross-linked to benzophenone incorporated adjacent to the exon-exon junction of spliced mRNA (Le Hir et al 2000a).…”
Section: Enhanced 5ј Exon Association Of Ref/aly and Srp20 Upon Exon mentioning
confidence: 99%
“…Prp8 is a U5 RNA-associated protein that contacts both the 5Ј and 3Ј splice sites of the intron (12)(13)(14)(15) as well as U6 RNA (16). Prp8 has been implicated in regulation of the second transesterification reaction (17)(18)(19)(20); our results suggest that Prp8 also functions in the first catalytic step of splicing.…”
mentioning
confidence: 60%
“…Several independent studies identified a SRp20-binding sequence with enhancer activity, all sharing the degenerate sequence CUC(U/ G)UC(C/T) (51)(52)(53)(54). In addition, application of the so-called SELEX strategy yielded SRp20-specific sequences with the consensus CA/UA/UC (55).…”
Section: Discussionmentioning
confidence: 99%